Geographic basis of euro region "Danube-Kris-Mures-Tisza" - Nađ Imre; Todorović Marina; Tošić Branka (Glasnik Srpskog Geografskog Društva, 2005)
Euroregion "Danube-Kris-Mures-Tisza" is formed both to stimulate local development and to serve as an example for cooperation to other areas in SEE. This project considers Banat as united region in three countries. Some differences which exist in separate parts of Banat (Hungary, Romania, Serbia) are less problem than this whole area that has advantages for favourable conditions for cooperation. In regard to some geographic characteristics this three parts of Banat are more similar to each other than to their own states. That fact contributes interregional cooperation in SEE.